2012
DOI: 10.3354/meps09480
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between induced phytoplankton blooms and the structure and dynamics of the free-living heterotrophic bacterial community

Abstract: Bacterial community activity and structure are thought to be directly or indirectly related to phytoplankton development and, in particular, to the phytoplankton species dominating specific algal blooms. To test this hypothesis, we performed a mesocosm experiment designed to generate blooms of different types of phytoplankton through the additions of silicate, urea and phosphorus to oligotrophic water from the Blanes Bay Microbial Observatory (NW Mediterranean). Over 10 d of incubation bacterial activity, bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
(35 reference statements)
1
9
0
1
Order By: Relevance
“…The DIATOM treatment was dominated by Chaetoceros sp. This taxon releases higher concentrations of DOM, measured as percentage of extracellular release (Wetz & Wheeler 2007), and also produces more extracellular polysaccharides than other diatom species (Myklestad 1995), enhancing bacterial activity (Lekunberri et al 2012, Sarmento & Gasol 2012. The DOM released in the DIATOM treatment was likely translated into 2-fold higher BP, since diatoms can produce highly labile substrates, such as polysaccharides (Myklestad 2000).…”
Section: Bacterial Bloom Phasementioning
confidence: 99%
“…The DIATOM treatment was dominated by Chaetoceros sp. This taxon releases higher concentrations of DOM, measured as percentage of extracellular release (Wetz & Wheeler 2007), and also produces more extracellular polysaccharides than other diatom species (Myklestad 1995), enhancing bacterial activity (Lekunberri et al 2012, Sarmento & Gasol 2012. The DOM released in the DIATOM treatment was likely translated into 2-fold higher BP, since diatoms can produce highly labile substrates, such as polysaccharides (Myklestad 2000).…”
Section: Bacterial Bloom Phasementioning
confidence: 99%
“…Our results accordingly imply that two phytoplankton derived DOM sources (Exp_CyDi) triggered more similar transcriptional responses by prokaryotes than did phytoplankton derived DOM compared with unamended seawater (control, Exp_SwDi). Similarly, a study focusing on taxonomic data showed that different phytoplankton blooms induced the development of similar prokaryotic communities that were nonetheless quite distinct from the unamended control community (Lekunberri et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The majority of prokaryotes growing in our continuous cultures were Gammaproteobacteria (Landa et al ., 2013a,b) which, based on transcript abundance, were also the most active community members. Members of Alphaproteobacteria and Bacteroidetes are often detected in association with the occurrence of marine phytoplankton blooms (Lekunberri et al ., ; Sarmento and Gasol, ; Teeling et al ., ) but were not abundant here. The continuous cultures possibly favoured Gammaproteobacteria by selecting for faster growing organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, ecosystem processes may also remain stable despite changes in community composition, indicating functional redundancy among bacterial populations (Fernandez et al ., 2000; Comte and del Giorgio, 2011). Moreover, the development of similar communities in response to different environmental conditions argues that bacterial generalists can also be important players in the cycling of DOC (Langenheder et al ., 2005; Mou et al ., 2008; Lekunberri et al ., 2012). So far, no clear patterns have emerged as to when and where populations responsive to disturbance are either resource specialists or generalists and how this affects ecosystem functioning.…”
Section: Introductionmentioning
confidence: 99%